2016
DOI: 10.1089/gtmb.2015.0253
|View full text |Cite
|
Sign up to set email alerts
|

MiRNA-Related Polymorphisms in miR-146a and TCF21 Are Associated with Increased Susceptibility to Coronary Artery Disease in an Iranian Population

Abstract: Our data provide the first evidence for the association of miR-146a rs2910164 and TCF21 rs12190287 with CAD in an Iranian population, encouraging further research to elucidate the disease-related effects of miR-146a rs2910164.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 33 publications
0
26
0
Order By: Relevance
“…In recent years, many studies found that miR-146a C>G polymorphism was closely related to the susceptibility of atherosclerotic diseases. In an Iranian population, miR-146a C>G polymorphism was associated with an increased susceptibility to CHD [ 30 ]. The gene polymorphism of miR-146a C>G was associated with an increased risk of CHD in the Chinese population, which might occur through influencing the expression level of the mature miR-146a [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, many studies found that miR-146a C>G polymorphism was closely related to the susceptibility of atherosclerotic diseases. In an Iranian population, miR-146a C>G polymorphism was associated with an increased susceptibility to CHD [ 30 ]. The gene polymorphism of miR-146a C>G was associated with an increased risk of CHD in the Chinese population, which might occur through influencing the expression level of the mature miR-146a [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs are a small noncoding RNAs involved in post‐transcriptional controlling of gene expression (Bastami et al, ). They were first reported in plants and then found in animals and even in viruses (Zaravinos, ).…”
Section: Mirnas In Emtmentioning
confidence: 99%
“…Studies on the effect of rs2910164 polymorphism on warfarin dose requirement in Iranian population are lacking. Some studies in Iranian population indicate that C allele of rs2910164 may be associated with coronary artery disease,23 while other studies indicate that C allele is associated with the risk of obesity 24. However, all these studies are performed in a limited number of patients and there are more studies and larger cohorts needed to evaluate the exact role of this polymorphism on cardiovascular diseases and warfarin dose requirements.…”
Section: Discussionmentioning
confidence: 99%